Direct and indirect acquisition of photoprotective compounds in crab larvae of coastal Patagonia (Argentina) - Hernández Moresino, Rodrigo Daniel (2014)
First larval stage (Zoea I) of the crab Cyrtograpsus altimanus can obtain photoprotective compounds (PPCs) from their mother (indirect acquisition) and also via feeding on PPC-producers such as phytoplankton (direct acquisition). The bioaccumulation of PPC resulted in higher survival of larvae exposed to ultraviolet radiation (UVR), when comparing larvae with high and low content of PPC. Thus, both ways of acquiring PPC may contribute to maximize survival of Zoea I when they are exposed to natural UVR.